Electrospinning with Droplet Generators: A Method for Continuous Electrospinning of Emulsion Fibers - Jensen, Bjarke N.; Pedersen, Thor L. V.; Fojan, Peter (Journal of Self Assembly and Molecular Electronics, 2022)
Emulsion electrospinning is a promising method for creating fibrous vehicles for delivery of drugs and bioactive compounds for the medical and food industries. Droplet microfluidics is a potent way of continuously generating controllable emulsion droplets. The incorporation of a droplet generator in an electrospinning setup for continuous electrospinning of emulsion fibers has been investigated. The influence of a droplet generator on the morphology of emulsion fibers has been established through electrospinning of emulsions of grapeseed oil in PVA and gelatine. The droplet generator was found to have no influence on the morphology of fibers. Conventional emulsification methods and droplet generator emulsification has been used to investigate the influence of emulsion droplet sizes on the morphology of emulsion fibers. Increasing the emulsion droplet size was found to create in-fiber droplets with diameters larger than the fiber diameter. The size of the in-fiber droplets was found to be dependent on both material and emulsion size.